Seismic fragility and resilience assessment of bridge columns with dual-replaceable composite link beam under near-fault GMs. (January 2023) - Zhong, Jian; Zheng, Xianglin; Wu, Qiaofei; Jiang, Linwei; He, Min; Dang, Xinzhi
Abstract: The beam-column joints of piers with reinforced concrete link beams (RCLB) are easy to be damaged during earthquakes. Post-earthquake maintenance is very inconvenient since the beam-column joints are integrally cast. Therefore, a novel dual-replaceable composite link beam (DRCLB) is proposed to replace the traditional RCLB, which is composed of angle steels, concrete-filled steel tubes (CFST), connection steel plates, and an RC beam. The dual-replaceable mechanism of DRCLB is that the angle steel and CFST of DRCLB are damaged in sequence, and can be quickly replaced separately after the earthquake. The multi-stage damage model of DRCLB is quantified by pushover analysis, which can be applied to seismic fragility and resilience assessment. The seismic fragility and resilience analysis are carried out under near-fault ground motions for double-column piers with DRCLB and RCLB respectively. The results indicate that DRCLB can effectively reduce the peak response of the beam-column joint. Meanwhile, the columns of double-column piers with DRCLB and RCLB respectively present approximately identical performance. Based on seismic resilience analysis, the recovery capacity of the pier is effectively improved due to the well dual-replaceable performance of DRCLB.